Efektivitas Musyawarah Guru Mata Pelajaran Pendidikan Agama Islam Dalam Meningkatkan Kompetensi Pedagogik Guru Pendidikan Agama Islam - Yuni; Mujahidin; Sera Yuliantini (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The aim of this research is the Islamic Religious Education Subject Teacher Deliberation in improving the pedagogical competence of PAI teachers; Describe the role of MGMP PAI in improving the pedagogical competence of high school level Islamic Religious Education teachers; Describe the supporting and inhibiting factors for PAI Subject Teacher Deliberations in improving the pedagogical competence of high school level teachers. This research uses a qualitative approach and descriptive research type. Data collection techniques use interviews and documentation. The data analysis technique used is data reduction. The data validity technique used is data reduction. The data validity techniques used are triangulation and member check. The results of this research show that: as a guide or direction for teachers, as well as directing, guiding teacher activities in the learning process to achieve goals, so that they can understand and comprehend the learning process conveyed by the relevant agencies in the Forum. Apart from that, the Forum is a form of effort carried out by the Ministry of Religion of Sambas district to improve the competencies of Islamic Religious Education Teachers at high school level; The PAI MGMP forum plays an important role in the process of improving teachers' teaching abilities. MGMP PAI acts as a reformer, mediator, collaborator, clinical and academic supervisor, evaluator and school developer, along with supporting agencies. So that teachers become enthusiastic and enthusiastic in carrying out their duties as educators; Supporting factors such as the existence of a legal umbrella that protects and further strengthens a PAI MGMP organization, namely the existence of the RI RELIGION MINISTER REGULATION Number 16 of 2010 concerning the PAI MGMP organization. Meanwhile, inhibiting factors in the PAI MGMP include the lack of budget support from the relevant agencies.